Cross Project and within Project Software Defection prediction using NLP Techniques - Yashwant Kumar, Dr. Vinay Singh , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The concept of cross project and within project software prediction is an important approach that is used to analyze the defects of software. The different scenario is used to analyze the functions of software prediction with the help of NLP Techniques. Defects are widespread in software systems and can cause a variety of problems for software users. The process software technology of predicting the defects are used to include different software components that helps in analyzing the functions of cross projects. There is a wide range of circumstances in the approach of suitable functions. It identifies the possibility of the system on the basis of different assurance of software prediction. The given article helps in analyzing the process of NLP techniques for the prediction of software. The different aspects are used to evaluate the framework which requires functions of cross projects.